Physical and chemical properties and antioxidant activity of modified and unmodified pectins extracted from orange bagasse - Venzon, Simoni Spohr (2013)
Modified pectin is a polysaccharide rich in galacturonic acid altered by pH adjustment and thermal treatment used especially as an anti-cancer agent. The aim of this work was to study the physical and chemical properties of modified and unmodified pectins extracted from orange bagasse by using citric and nitric acids. The galacturonic acid content, degree of esterification, Fourier Transform Infrared 30 Spectroscopy profile, molar mass, intrinsic viscosity, rheological properties and antioxidant activity of the pectins were evaluated. The modification process caused the de-esterification of pectins, responsible for improving the intestinal absorption of modified pectin and a decrease of molecular weight due to removal of neutral sugars, maintaining the linear chain of galacturonic acid. Such changes also caused a significant increase in the in vitro antioxidant activity and influenced the rheological properties of pectin, reducing its viscosity. This work showed that the modification of pectin from orange bagasse with citric and nitric acids altered its structural and physical characteristics as well as its biological activity toward a free-radical, suggesting that some functional properties related to antioxidant activity activity and absorption of nutrients may be increased.